Exploring the Link between Financial Reporting Models and Earnings Characteristics among Tehran Stock Exchange Listed Companies - Roya Amiri; Ali Ashtab; Mahdi Heydari (تحقیقات مالی)
ObjectiveObjective: In recent years, the focus on earnings characteristics has intensified, spurred by the financial disclosures of some major corporations. Financial analysts and investors not only consider the accounting profit figure when assessing future cash flows but also prioritize the sustainability and repeatability of reported earnings. More than the final earnings figure, they refer to the items that make up real earnings, usefulness in predicting future earnings, as well as the stability, sustainability, and immutability of reported earnings. Earnings are one of the most important factors affecting economic decisions. Users' awareness of the reliability of earnings can help analysts make better decisions about profitability and financial statement analysis. This study examines the relationship between financial reporting models and earnings characteristics of companies listed on the Tehran Stock Exchange. MethodsThe present study is applied in terms of purpose. In the present study, the required data have been extracted from Rahavard Novin software, financial statements of companies and text mining as well as the Codal website. The statistical population of the present study includes companies listed on the Tehran Stock Exchange from 2012 to 2022. Stata 14 was the software utilized for data preparation and model estimation in this study. The panel data model was used to test the research hypotheses. ResultsThe findings of this study indicate that the net assets approach negatively impacts the quality of accruals, positively influences income smoothing, negatively affects earnings predictability, and does not impact earnings sustainability. Additionally, the results obtained indicate that the transactional approach positively affects the quality of accruals, has no effect on income smoothing or earnings predictability, and negatively impacts earnings sustainability. ConclusionThis study has examined earnings characteristics from four perspectives: accruals quality, income smoothing, earnings predictability, and earnings sustainability. Accruals quality associates accruals with past, present, and future cash flows, and then tests them. This criterion (called accruals quality) is related to debt cost and equity cost. Earnings sustainability indicates the stability and persistence of earnings. Because management cannot address all the requirements of financial statement users, reliance on financial information as companies' output is heightened. Thus, the significance of earnings quality is paramount prior to decision-making, as higher earnings quality correlates with better company performance. For reasons such as retention in the company, bonus receipt, and other factors, the manager consciously or unconsciously presents the status of the company as favorable; therefore, the characteristics of corporate earnings are influenced by the foundations of reporting and the discretion of their managers. Less reliable earnings equate to less useful information they offer.